مدى تماشي النظام المحاسبي الموحد للمصارف و شركات التامين مع معايير الافصاح العالمية: دراسة تحليلية للمعيار رقم 30 الخاص بالإفصاح عن القوائم المالية في البنوك - نادية سامي خضر (PROSPECTIVE RESEARCHES, 2023)
Accounting disclosure is regarded as a main component to achieve the objective of financial records of saving appropriate information to the sides who use it to make economic decisions, which indicate clearly the economic unit to the users. The importance of disclosure increases in relation with commercial banks considering its work in the field of financial mediation, where most society reserve are collected and present credit to all branches of economic activity. To reach the international development of banking field, the committee of international accounting standards cares to issue a number of bank standards concerning disclosure and the bases of accounting measure. This progress of banking surroundings in the local and global level raises the question of degree of disclosure adequate in the Iraqi commercial banks to the local and global variables in response with the international disclosure standards issued by the committee of international accounting standards.